2021
DOI: 10.1007/s11701-021-01295-4
|View full text |Cite
|
Sign up to set email alerts
|

Incremental modification of robotic prostatectomy technique can lead to aggregated marginal gains to significantly improve functional outcomes without compromising oncological control

Abstract: Introduction and objectivesSurgeons should aim for continuous quality improvement. The aim of this study was to evaluate the impact of incremental changes to Robot Assisted Radical Prostatectomy (RARP) technique on intra-operative and early post-operative outcomes. Patients and methods All cases of RARP performed by a single surgeon in a tertiary institution over a 2-year period were included in this evaluation. Routine clinical data were collected. Cases were retrospectively allocated to four groups depending… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 25 publications
(34 reference statements)
2
12
0
Order By: Relevance
“…The aim of the current study was to describe the characteristics and outcomes of the first 130 RS-RARP cases performed at our institution; and to draw a comparison between the first, second and third groups of this series. The results demonstrate that patient characteristics were broadly representative of patients undergoing RARP at our institution (9,10). The first group of patients were youngest, with the lowest proportion of clinically locally advanced disease and smallest gland size.…”
Section: Discussionmentioning
confidence: 69%
See 4 more Smart Citations
“…The aim of the current study was to describe the characteristics and outcomes of the first 130 RS-RARP cases performed at our institution; and to draw a comparison between the first, second and third groups of this series. The results demonstrate that patient characteristics were broadly representative of patients undergoing RARP at our institution (9,10). The first group of patients were youngest, with the lowest proportion of clinically locally advanced disease and smallest gland size.…”
Section: Discussionmentioning
confidence: 69%
“…Galfano's group found no difference between their first and second 100 RS-RARP patients (6). Analysis of our institutions first 22 and 70 cases found that that outcomes compared favourably with standard RARP from the start (9,10). The aim of the present study was to build on the understanding of the learning-curve for RS-RARP by describing the characteristics and outcomes of the first 130 RS-RARP cases, with specific comparison between the first, second and third groups of this series.…”
Section: Introductionmentioning
confidence: 68%
See 3 more Smart Citations